Assessing multidrug administration preferences among incarcerated Filipino elderly: a choice experiment study. Issue 6 (3rd June 2019) - De Guzman, Allan B.; Gatus, John Lyndon G.; Genilo, Michael Kim C.; Golosinda, Ethyl Joy H.; Gonzales, Razel Carmela B.; Gonzalez, Estephanie Sarah P.
ABSTRACT: While there had been numerous studies about the prevalence of polypharmacy among the elderly around the world, the need to know about their preference about multidrug administration remains a research imperative. This study aims to test the feasibility of using conjoint analysis (CA) to assess the elderly patients' preferences for multiple drug administration. To gather the needed data for the study, the multiple factor full-concept method was used. By means of an orthogonal main effects design, 20 choice sets were randomly chosen from the 96 possible descriptions generated via Sawtooth Software Version 18 and were ranked by 350 incarcerated Filipino elderly. Results of this study indicated the conjoint model performed was adequately fit; Pearson R = .999, p < .05 and Kendall's t was 1.00, p < .05. Among the attributes of multidrug administration, patient education is the most important factor considered by incarcerated Filipino elderly (34.78%), followed by the number of drugs taken at a time (29.47%), and nurse–patient relationship (19.07%). In regard to the part-worth of patient education, the more health teachings are given, the higher is the adherence to multidrug administration. As for the number of drugs taken at a time, the lower the quantity of drugs, the higher is the adherence. The active relationship with the nurse to the patient was preferred over nurse passivity. This information is vital to the development of a model that will guide health-care providers on the preference of elderly on multidrug administration to ensure better medication adherence.